The Effect of Arias (Assurance, Relevance, Interest, Assesment, Satisfaction) Learning Model and Portofolio Assesment To Learning Outcomes And Creative Thinking Ability Of High School Student (Subject of Immunity System for 2nd of SMA Negeri 3 Jember) - Dyah Chandra Palupi; Wachju Subchan; Siti Murdiyah (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2018)
This quasy experiment study aimed to analyze the effect of ARIAS (Assurance, Relevance, Interest, Assesment, Satisfaction) learning model withPortofolioAssesmentto learning outcomes and creative thinking ability. Subjects in this study were 36 students of XI IPA 4and 36 students of XI IPA 5 SMA Negeri3Jember. Data collection techniques used were interview, observation, documentation, and tests. Data were analyzedusing descriptive with quantitative and qualitative approach. Based on the results of the study showed that there was significant effect of ARIAS (Assurance, Relevance, Interest, Assesment, Satisfaction) learning model withPortofolio towards learning outcomes and creative thinking of students at XI IPA SMA Negeri 3 Jember.